Different modalities of exercise improve macrovascular function but not microvascular function in metabolic syndrome: The RESOLVE randomized trial. (15th September 2018) - Vinet, Agnès; Obert, Philippe; Courteix, Daniel; Chapier, Robert; Lesourd, Bruno; Verney, Julien; Dutheil, Frédéric; Walther, Guillaume
Abstract: Objective: To determine which modality of exercise program (endurance and/or resistance dominance) is the most effective for improving vascular function in the micro- and macrocirculation in metabolic syndrome (MetS). Methods: Sixty-two MetS patients were enrolled in a 6-month lifestyle intervention program based on diet and exercise training. Each participant was randomly assigned to one of 3 groups categorized by exercise modality (e.g. high-intensity resistance or endurance training, or combined moderate-intensity). Measurements of anthropometrics, biological blood markers, physical fitness and vascular function were performed at baseline, at the end of the 3-week residential program, and at 3 and 6 months after baseline. Brachial artery flow-mediated dilation (FMD) and the response to sublingual nitrate were assessed by high-resolution ultrasound. Microvascular reactivity was evaluated using laser Doppler flowmetry in conjunction with iontophoresis of acetylcholine and sodium nitroprusside. Results: Regardless of the training program, FMD significantly increased from baseline to 3 weeks in all groups with no further changes at 3 and 6 months. Changes in central fat, diastolic blood pressure, triglycerides, interleukin-6 and physical fitness were independent predictors of increased FMD. Nitrate-mediated dilation increased from baseline to 3 months and then remained unchanged up to 6 months. Endothelium-dependent and endothelium-independent function of the skin microcirculation did not change significantly in all groups. Conclusions: In MetS patients, exercise training, regardless of its endurance or resistance dominance, is able to improve vascular function in large vessels only. Lifestyle intervention programs including exercise training must be encouraged in those with MetS. NCT00917917. Highlights: Exercise training produced distinctive vascular functional effects. Exercise training improved macrovascular dysfunctions in metabolic syndrome. Reduction in central fat and inflammation contributed to macrovascular improvement. Exercise training did not improve microvascular dysfunctions in metabolic syndrome.